Use of Marine Biological Resources of the Arctic Region for Creation of Combined Fish and Vegetable Canned Pastes - Kuranova, Lyudmila; Grokhovsky, Vladimir; Ershov, Mihail; Pilipenko, Anastasia (KnE Life Sciences, 2020)
The article discusses the possibility of expanding the species composition of sterilized food products through harvesting and processing of fucus algae growing in the Arctic littoral. Their rich chemical composition is shown, having a high content of such essential nutrients as polysaccharides, iodine, and water-soluble vitamins. Microbiological and toxicological studies of fucus algae F. vesiculosus and A. nodosum conducted by the authors have proved the safety and possibility of using fucus algae in food production. The article presents the results of the newly-developed manufacturing technology for canned fish pastes with vegetable components on the example of Northern blue whiting (Micromesistius poutassou) and the Barents Sea algae (Fucus vesiculosus). The authors worked out the technological scheme, optimized the product formulation, provided the scientific substantiation for the product sterilization regime, and evaluated the quality of the finished product. The combination of fucus properties with fish tissues enabled the authors to bring closer the solution to the problem of developing food products with a balanced nutrition formula. The functionality of the developed sterilized product based on the content of iodine, calcium, magnesium and phosphorus is shown.